2003
DOI: 10.1098/rsbl.2003.0031
|View full text |Cite
|
Sign up to set email alerts
|

Strong mothers bear more sons in rural Ethiopia

Abstract: In humans, there is evidence that the physiological cost to the mother of bearing sons is greater than of bearing daughters. Parents should manipulate the sex of offspring born in response to resource availability to maximize their reproductive success. Here, we demonstrate that, within a rural foodstressed community in southern Ethiopia, there is a strong association between the sex of the most recent birth and maternal nutritional status, measured either by body mass index or mid-upper arm muscle area (AMA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
65
3
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(73 citation statements)
references
References 18 publications
4
65
3
1
Order By: Relevance
“…Such demand may be imposed either directly, through behaviors that solicit forms of investment as in Angelman syndrome, or indirectly, through selforiented, non-social behavior that precludes or delays physical independence, requiring mothers or others to provide longer-term, more highly-intensive care. This 18 hypothesis is concordant with several lines of evidence, including: (1) accelerated brain and body growth in young children with autism and increased relative effects from paternally-expressed imprinted genes (Crespi and Badcock 2008), (2) imprinted gene effects on reaction to novelty, and dispersal, in mice (Isles et al 2002;Plagge et al 2005), (3) a higher incidence of autism in males, who are more costly than females to rear (Gibson and Mace 2003;Rickard et al 2007;Tamimi et al 2003), (4) myriad reports of close and sustained, if atypical, relationships between mothers and their autistic children (e. g., Hoffman et al 2009), and (5) temperaments of autistic children that involve higher rates of activity, impulsivity, and non-compliance (e. g., Garon et al 2009).…”
Section: Autism and Attachmentsupporting
confidence: 66%
“…Such demand may be imposed either directly, through behaviors that solicit forms of investment as in Angelman syndrome, or indirectly, through selforiented, non-social behavior that precludes or delays physical independence, requiring mothers or others to provide longer-term, more highly-intensive care. This 18 hypothesis is concordant with several lines of evidence, including: (1) accelerated brain and body growth in young children with autism and increased relative effects from paternally-expressed imprinted genes (Crespi and Badcock 2008), (2) imprinted gene effects on reaction to novelty, and dispersal, in mice (Isles et al 2002;Plagge et al 2005), (3) a higher incidence of autism in males, who are more costly than females to rear (Gibson and Mace 2003;Rickard et al 2007;Tamimi et al 2003), (4) myriad reports of close and sustained, if atypical, relationships between mothers and their autistic children (e. g., Hoffman et al 2009), and (5) temperaments of autistic children that involve higher rates of activity, impulsivity, and non-compliance (e. g., Garon et al 2009).…”
Section: Autism and Attachmentsupporting
confidence: 66%
“…Three independent measures of household wealth and status were included: land holding size, total number of fathers' marriages, and sibling sex ratio at birth (including dead siblings). The latter was included as a previous study had indicated that a secondary sex ratio biased toward males was a measure of well-being in this population (46).…”
Section: Methodsmentioning
confidence: 99%
“…Weak relationships between sex ratios and the nutritional resources of mothers in late pregnancy and postnatally have been reported (Gibson & Mace 2003;Tamimi et al 2003) but are controversial (Stein et al 2003). Even if real, they do not imply any maternal command over foetal sex.…”
Section: Introductionmentioning
confidence: 99%